(untitled) (Revista de Ensino em Artes, Moda e Design, 2021)
This article aimed to report how the sketchbook can be used as a tool for recording information about the artisan community of the Rio Vermelho community in the city of Florianópolis (BR). For this, in the collection of research data, interviews with visits to the community were used. To form the body of knowledge, a narrative and unsystematic bibliographic review was used. Methodologically, this article can be understood as applied, qualitative, descriptive and field research. From the experience report presented, it appears that, different that the use of the sketchbook in the phase of project ideation in the work of designers and artists, as indicated by the investigated literature, the tool can also be used as an instrument for recording and documenting textual and visual information about the artisan knowledge of bobbin lace. It was also concluded that the sketchbook can be relevant as a source of documentary research and as a tool to safeguard how to produce artisanal contemporary artifacts.